Functional and selective neck dissection - Gavilán, Javier (Thieme, 2020)
"This updated second edition presents a unique point of view based on fascial dissection techniques developed by several generations of renowned surgeons at La Paz University Hospital, Spain. This book lays a foundation with in-depth discussion of fascial compartmentalization of the neck. The text covers the evolution of modern neck dissection, from George Crile in 1906 to current cutting-edge procedures, and details the transition from radical neck dissection to a less aggressive, equally effective approach for treating lymph node metastases in head and neck cancer. The relationship between functional and selective neck dissection is discussed from a pragmatic and nonconventional perspective, elucidating the connection from historical, anatomic, and surgical standpoints. The four authors differentiate conceptual approaches, keystones in the evolution of scientific knowledge from surgical techniques, technical variations of a standard procedure designed to most effectively resolve a problem. The primary goal of this book is providing the reader with expert guidance on a full spectrum of fundamental surgical techniques"--